Where “the blood boils:” Hans Christian Andersen’s sojourn in Naples - Clemente, Frances (Quaderni d'Italianistica)

(untitled) (Iter Press, 2020)
When in 1834, during his Grand Tour of Europe, Hans Christian Andersen set foot in Naples, he was immediately won over by the exuberant vitality of the Neapolitan people. The Parthenopean city, where he “was exposed to sensuality as a daily temptation” (Rossel, “Hans Christian Andersen” 24 and “Do You Know the Land” 95), also awakened Andersen’s more repressed instincts. From this experience he drew material for his most autobiographical novel, Improvisatoren (1835; The Improvisatore), whose protagonist tries to and succeeds in resisting the seductions of Neapolitan sensuality. If on the one hand the Danish author underwent the typical experience of the Northern traveller visiting the South and, more specifically, Naples, enjoying its openness and gaiety, on the other hand he never completely abandoned himself to Southern allures, upholding his moral and religious beliefs against a city that continuously attempted to wholly seduce him. The present paper aims to retrace Andersen’s first journey to Naples—where, by the writer’s own account, “the blood boils” (The Diaries of Hans Christian Andersen 85)—as a voyage into a tempting sensuality, contextualizing it within the wider context of nineteenth-century travelling experience in the city by Northern travellers.